Analisis Tekno-Ekonomi Produksi Gula Reduksi dari Biomassa Ampas Tebu Melalui Hidrolisis Air Subkritis - Maktum Muharja; Siska Nuri Fadilah; Nur Fadhilah; Rizki Fitria Darmayanti; Arief Widjaja; Achri Isnan Khamil (Universitas Trunojoyo Madura, 2023)
Subcritical water hydrolysis of bagasse requires energy to convert lignocellulosic biomass into fermentation-ready sugars. Bagasse biomass has the potential to be used as raw material for the production of reducing sugar. This study evaluates the effectiveness of the hydrolysis process using an oven and autoclave through economic and energy analysis. The variables used were hydrolysis time of 20-60 minutes, oven temperature of 110-170°C, and autoclave temperature of 120-130°C. Reduced sugar concentration was obtained from analysis using the DNS (dinitro salicylic acid) method. The results of the analysis show that time and temperature have a significant effect on the yield of reducing sugar. The highest reduced sugar concentration from subcritical water hydrolysis using an oven was 27.4 g/L at 170°C operating conditions for 60 minutes with a total cost of Rp 351,744 and energy requirement of 480 W.h. In hydrolysis using an autoclave, it was obtained at 14.7 g/L at 125°C for 40 minutes with a total cost of IDR 923,079 and energy requirements of 1,936.67. Hydrolysis using an oven is more recommended than autoclaving because it is economical and has lower energy consumption.